Analisis Saluran Pemasaran Salak Pondoh (Salacca edulis Reinw) Desa Rumah Lengo Kecamatan STM Hulu : Marketing Channel Analysis of Pondoh Salak (Salacca edulis Reinw) Rumah Lengo Village, STM Hulu District - Barus, Umike Rosella Br; Nurcahyani, Marizha (Universitas Medan Area, 2025)
This research aims to determine: 1) the marketing channel pattern for pondoh salak in Rumah Lengo Village, STM Hulu District, 2) the income of salak farmers, 3) the margin of each marketing channel formed, 4) farmer's share of each marketing channel, 5) the level of efficiency of each marketing channel. The analytical method used in this research is descriptive and quantitative analysis. Descriptive analysis to determine marketing institutions and marketing channels for salak. Quantitative analysis to analyze income, marketing margin, farmer's share and marketing efficiency analysis. The results of this research show that there are three marketing channel patterns for pondoh salak in Rumah Lengo Village, namely: Marketing channel pattern I: Farmers → Final consumers, Marketing channel pattern II: Farmers → Retailers → Consumers, Marketing channel pattern III: Farmers → Collecting traders → Retailers →Consumers The average revenue of Pondoh salak farmers per hectare is IDR 2,223,529, with a total farming cost of IDR 636,765, resulting in an average income of IDR 1,577,848. The highest farmer's share is found in marketing channel I, where farmers sell directly to consumers, making it the shortest and most profitable channel. All three marketing channels in the research area are efficient, but the most efficient is marketing channel I with an efficiency value of 1%, followed by channel II with 4.6%, and the lowest is channel III with 8.99%.